2013
DOI: 10.2217/imt.13.126
|View full text |Cite
|
Sign up to set email alerts
|

Up to 15-year Clinical Follow-Up of a Pilot Phase III Immunotherapy Study in Stage II Breast Cancer Patients Using Oxidized Mannan–MUC1

Abstract: The preliminary evidence indicates that M-FP is beneficial in the overall survival of early-stage breast cancer patients. This long-term clinical follow-up of patients strongly supports the necessity for a large Phase III study of direct M-FP injection in early-stage breast cancer patients, to evaluate immunotherapy as an adjuvant treatment for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 19 publications
0
76
0
1
Order By: Relevance
“…DC in particular are proficient in processing exogenous antigens for presentation by class I molecules via the cross-presentation pathway [58]. Most adjuvants have properties or are designed to access one or both of these pathways using a number of mechanisms such as the nature of the particulate (microparticles, VLP, ISCOM) [59][60][61][62], having membrane fuseogenic properties (liposomes, ISCOM) [63,64] or cell surface receptor binding (mannan or recombinant antibody) [3,4,6,8].…”
Section: Efficient Generation Of Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…DC in particular are proficient in processing exogenous antigens for presentation by class I molecules via the cross-presentation pathway [58]. Most adjuvants have properties or are designed to access one or both of these pathways using a number of mechanisms such as the nature of the particulate (microparticles, VLP, ISCOM) [59][60][61][62], having membrane fuseogenic properties (liposomes, ISCOM) [63,64] or cell surface receptor binding (mannan or recombinant antibody) [3,4,6,8].…”
Section: Efficient Generation Of Cd8mentioning
confidence: 99%
“…Studies have identified receptors on various DC subtypes that are efficient in generating immune responses [3,4]. There are also multiple approaches reported for the targeted delivery of antigens to some of these receptors expressed on DC and few vaccines are currently in clinical trials [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…При окислительном связывании с рекомбинантным белковым антигеном и последующем интраназальном его введении маннан усиливал выработку антиген-специфических сывороточных и секреторных антител у мышей F1 и C57BL. В клиническом исследовании антигена MUC-1 (антиген, экс-прессируемый различными опухолями, в данном случае аде-нокарциномой), конъюгированного с окисленным маннаном, частота рецидивирования опухоли была более чем в четыре С. С. Курашова, Т. К. Дзагурова, А. А. Ишмухаметов, М. С. Егорова, М. В. Баловнева, С. Е. Соцкова, Е. А. Ткаченко S. S. Kurashova, Т. К. Dzagurova, А. А. Ishmukhametov, М. S. Egorova, М. V. Balovneva, S. E. Sotskova, Е. А. Tkachenko раза ниже [43]. При конъюгации основного миелинового белка (ОМБ) с восстановленным маннаном иммунный ответ против ОМБ реализовывался не Th1, а Th2, что предотвращало раз-витие экспериментального аллергического энцефаломиелита у мышей [44].…”
Section: маннановые адъювантыunclassified
“…The median survival times were 23.1 months and 22.3 months, respectively [Miles et al 2011]. An oxidized mannan-MUC1 vaccine showed, in the adjuvant setting, an encouraging reduction in recurrence rate (12.5% versus 60% in the placebo arm) after 15 years of follow up [Vassilaros et al 2013].…”
Section: Ctla-4mentioning
confidence: 99%